2013
DOI: 10.4172/2157-2518.s6-005
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin Induces Apoptosis in Prostate Cancer Cells by Downregulating Bcl-2 through ROS-dependent Ubiquitin-proteasomal Degradation Pathway

Abstract: Pristimerin is a quinonemethide triterpenoid with the potential of a promising anticancer agent. Pristimerin (PM) has shown anticancer activity against a range of cancer cell lines, but its activity for prostate cancer has not been adequately investigated. In the present study we have examined the underlying mechanisms of the apoptotic response of the hormone-sensitive (LNCaP) and hormone-refractory (PC-3) prostate cancer cell lines to PM. Treatment with PM induced apoptosis in both cell lines as characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…It was noted that the increase in Bax/Bcl-2 ratio was mainly due to the down-regulation of Bcl-2 at protein level, but not at the mRNA level. Thus, it is suggested that Bcl-2 protein is posttranslationally modified by either phosphorylation or ubiquitination via MAPKs and AKT, resulting in a proteosomal degradation of Bcl-2 protein which increases the BAX/BCL-2 ratio to initiate the mitochondrial apoptotic pathway (Deeb et al, 2014;Liu et al, 2013;Gao and Dou, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that the increase in Bax/Bcl-2 ratio was mainly due to the down-regulation of Bcl-2 at protein level, but not at the mRNA level. Thus, it is suggested that Bcl-2 protein is posttranslationally modified by either phosphorylation or ubiquitination via MAPKs and AKT, resulting in a proteosomal degradation of Bcl-2 protein which increases the BAX/BCL-2 ratio to initiate the mitochondrial apoptotic pathway (Deeb et al, 2014;Liu et al, 2013;Gao and Dou, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We show that activation of both caspase-8 and caspases 3/7 by Fas-activating antibody is impeded by the CKGC peptide. ROS can inactivate anti-apoptotic Bcl-2 and prevent procaspase-3 processing ( Liu et al, 2013 ; Martinez-Reyes and Cuezva, 2014 ). Also, excessive ROS leads to down-regulation of c-FLIP, the inhibitor of caspase-8 ( Circu and Aw, 2010 ; Wilkie-Grantham et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antiproliferative activity of pristimerin goes beyond colon-related cancers, it is extended to breast [346][347][348][349][350], melanomas [351], osteosarcoma [352], pancreatic [353,354], and prostate cancers [355][356][357][358]. Herein, we describe a few examples focusing on articles that have demonstrated potential mechanisms of action.…”
Section: Pristimerinmentioning
confidence: 99%
“…Its progression was reported to be prevented by pristimerin-induced inhibition on HIF-1α and SPHK-1, which stimulates different cellular processes including cell proliferation, cell survival, and angiogenesis [355,369]. Pristimerin also induced apoptosis of prostate cancer cells through activation of mitochondrial apoptotic pathway [358], ubiquitin-proteasomal degradation [357], and inhibition of proteasomal chymotrypsin-like activity (a complex associated with cell proliferation, apoptosis, and cancer progression) [370,371]. These summarized findings provide evidences regarding pristimerin antiproliferative and cytotoxic activity as well as clinical benefits for treatment of different types of cancer.…”
Section: Pristimerinmentioning
confidence: 99%